Habitat suitability and influencing factors of a threatened highland flagship species, the Black-necked Crane (Grus nigricollis) - Hongying Xu; Ru Jia; Hongrui Lv; Ge Sun; Dongping Liu; Hongyan Yu; Cunxin Ma; Tian Ma; Wenhong Deng; Guogang Zhang (Avian Research)
Evaluating the habitat suitability of flagship species and its key influencing factors is vital for understanding potential conservation issues and developing coping strategies. We surveyed the wintering population size and distribution of the Black-necked Crane (Grus nigricollis) in the Yarlung Zangbo River Basin (YZRB) from 10 to 29 January 2022, and predicted the current potentially suitable habitat distribution and its effective factors using the MaxEnt model. A total of 9337 wintering Black-necked Cranes were recorded in the YZRB in 2022, 76.58 % of which were primarily found in Lhunzub, Samzhubze, Namling, and Lhaze. Compared to 2018, the crane population has exhibited a notable decline in Samzhubze and Taktse, likely due to farmland plowing, winter irrigation, changes in agricultural practices, road construction and hydraulic projects. The crane population within various counties exhibited a significant positive correlation with the suitable habitat area (r = 0.70, P = 0.002, n = 17). We also found that the currently suitable habitat area covered 17,204 km2, of which only 3244 km2 (18.86 %) was effectively protected at the national level, which was predominantly distributed in farmland and rangeland habitats characterized by gentle slopes, altitudes not exceeding 4500 m, and proximity to human settlements along rivers, where suitable isothermal values (51) and less seasonal precipitation (20 mm) prevail. Our study will be helpful for formulating reasonable conservation strategies to protect the core population of this threatened highland flagship species.